Artificial aortic valve dysfunction due to pannus and thrombus – different methods of cardiac surgical management - Ostrowski, Stanisław; Marcinkiewicz, Anna; Kośmider, Anna; Walczak, Andrzej; Zwoliński, Radosław; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction: Approximately 60 000 prosthetic valves are implanted annually in the USA. The risk of prosthesis dysfunction ranges from 0.1% to 4% per year. Prosthesis valve dysfunction is usually caused by a thrombus obstructing the prosthetic discs. However, 10% of prosthetic valves are dysfunctional due to pannus formation, and 12% of prostheses are damaged by both fibrinous and thrombotic components. The authors present two patients with dysfunctional aortic prostheses who were referred for cardiac surgery. Different surgical solutions were used in the treatment of each case. Case study 1: The first patient was a 71-year-old woman whose medical history included arterial hypertension, stable coronary artery disease, diabetes mellitus, chronic obstructive pulmonary disease (COPD), and hypercholesterolemia; she had previously undergone left-sided mastectomy and radiotherapy. The patient was admitted to the Cardiac Surgery Department due to aortic prosthesis dysfunction. Transthoracic echocardiography revealed complete obstruction of one disc and a severe reduction in the mobility of the second. The mean transvalvular gradient was very high. During the operation, pannus covering the discs’ surface was found. A biological aortic prosthesis was reimplanted without complications. Case study 2: The second patient was an 87-year-old woman with arterial hypertension, persistent atrial fibrillation, and COPD, whose past medical history included gastric ulcer disease and ischemic stroke. As in the case of the first patient, she was admitted due to valvular prosthesis dysfunction. Preoperative transthoracic echocardiography revealed an obstruction of the posterior prosthetic disc and significant aortic regurgitation. Transesophageal echocardiography and fluoroscopy confirmed the prosthetic dysfunction. During the operation, a thrombus growing around a minor pannus was found. The thrombus and pannus were removed, and normal functionality of the prosthetic valve was restored. Conclusions : Precise and modern diagnostic methods facilitated selection of the treatment method. However, the intraoperative view also seems to be crucial in individualizing the surgical approach.